CULTURAL RESONANCE IN POPULIST COMMUNICATION: A COMPARATIVE STUDY OF POLITICAL RHETORIC ACROSS REGIONS - Abdul Rahman (Penelitian dan Pengembangan Ilmu, 2025)
This research examines the dynamics of global populism, which has transformed from mere economic articulation into a communication practice based on cultural identity through the mechanism of cultural resonance. Utilizing a narrative review approach that synthesizes literature from Scopus and Web of Science databases within the 2016-2026 period, this study analyzes how political actors build affective proximity through authenticity strategies and local symbolism. The findings indicate that while populism possesses a universal structure the dichotomy between